2012
DOI: 10.1007/s11105-012-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Bioinformatic Characterization of Type II Metacaspase Protein (TaeMCAII) from Wheat

Abstract: The biochemical analysis and homology modeling of a tertiary structure of a cereal type II metacaspase protein from wheat (Triticum aestivum), TaeMCAII, are presented. The biochemical characterization of synthetic oligopeptides and protease inhibitors of Escherichia coli-produced and purified recombinant TaeMCAII revealed that this metacaspase protein, similar to other known plant metacaspases, is an arginine/lysine-specific cysteine protease. Thus, a model of a plant type II metacaspase structure based on new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The activity of the majority of type I and type II metacaspases characterized to date has been shown to be affected by the presence of calcium ions. Although TbMC2 is the only type I metacaspase requiring high micromolar concentrations of CaCl 2 for activity (Machado et al ., ), yeast type I metacaspase Yca1, as well as type II metacaspases and the type III metacaspases reported here, require millimolar concentrations for full proteolytic activity (Watanabe & Lam, ; Zhang & Lam, ; Piszczek et al ., ). The only exception is the A. thaliana type II metacaspase AtMC9, whose activity has been reported to be calcium independent (Zhang & Lam, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The activity of the majority of type I and type II metacaspases characterized to date has been shown to be affected by the presence of calcium ions. Although TbMC2 is the only type I metacaspase requiring high micromolar concentrations of CaCl 2 for activity (Machado et al ., ), yeast type I metacaspase Yca1, as well as type II metacaspases and the type III metacaspases reported here, require millimolar concentrations for full proteolytic activity (Watanabe & Lam, ; Zhang & Lam, ; Piszczek et al ., ). The only exception is the A. thaliana type II metacaspase AtMC9, whose activity has been reported to be calcium independent (Zhang & Lam, ).…”
Section: Discussionmentioning
confidence: 97%
“…Increasing biochemical evidence has shown that the catalytic activity of type I and type II metacaspases depends on the presence of calcium ions, with the only exception of an Arabidopsis thaliana type II metacaspase, AtMC9, whose activity is calcium independent (Zhang & Lam, ). In type II metacaspases, the presence of CaCl 2 in millimolar concentrations induces specific cleavage in the linker region between p20 and p10 domains, similar to the activation observed in caspases (Vercammen et al ., ; Lam & Zhang, ; Piszczek et al ., ). Although cleavage between the two domains in type I metacaspases does not seem to be essential for activation, the presence of calcium is a fundamental requirement for their catalytic activity (Moss et al ., ; Wong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Authors have mentioned two isoforms of 35 and 27 kDa isolated by affinity chromatography in denaturing conditions. Type II metacaspase from wheat leaves (TaeMCAII) was modeled in silico, cloned and characterized (Piszczek et al 2011;Piszczek et al 2012). Studies of Arabidopsis thaliana dwarf mutant, impaired in carbohydrate metabolism, enabled characterization of NANA, chloroplastlocated, aspartic proteinase (Paparelli et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Animal caspases are cysteine endopeptidases cleaving their substrates on the carboxyl side of aspartate residues (Kaufmann & Hengartner, 2001). Studies with recombinant plant metacaspases, including TaeMCAII, showed that metacaspases are unable to cleave caspase substrates and that their preferred cleavage site was after Arg or Lys residues (Vercammen et al, 2004;Bozhkov et al, 2005;Vercammen et al, 2006;Piszczek et al, 2012). Arginine and lysine have positively charged side-chains; thus, negatively charged residues surrounding the active site can facilitate ligand binding.…”
Section: Resultsmentioning
confidence: 99%